Pupillary Activity Dynamics in a Multitask Environment - Miltenburg, M.P.G. van; Bos, T.J.J.; Klaren, C. van; Verhoeven, R.P.M. (My University, 2024)
This research delves into the Index of Pupillary Activity (IPA) as a novel, realtime metric for assessing cognitive workload in multitasking environments. Traditional metrics like pupil size are influenced by external factors, making them less reliable. In contrast, IPA directly reflects mental effort and attention, offering insights into cognitive workload fluctuations. This study aims to validate IPA’s sensitivity to changes in cognitive demands across various task complexities and its correlation with subjective workload measures. By emphasizing IPA, this research could significantly enhance strategies for optimizing task performance and deepen our understanding of human cognition.